The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.46827/ejes.v8i3.3647
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship Between the Intolerance of Uncertainty and Levels of Health Perception Faculty of Sports Sciences Students During the Pandemic Process

Abstract: The purpose of this research examining the relationship between the level of intolerance to uncertainty and health perceptions during distance education university students and explaining whether intolerance to uncertainty predicts perception of health. This study is descriptive research in the relational survey model. The sample group consisted of 276 students, 138 (50%) of whom were female, and 138 (50%) of whom were male, studying distance education in the spring term of 2019-2020. Personal information form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Existing research in the area of students' mental health demonstrates the positive relationship between academic grit and psychological well‐being (Jelińska & Paradowski, 2021 ; Lan & Moscardino, 2019 ; J. Li & Li, 2021 ) and the negative relationship between intolerance to uncertainty and psychological well‐being (Ulukan, 2021 ; Zhuo et al, 2021 ). Less is known about this relationship, mainly about the mediators, but these factors are important to understand why and how students' engagement improves students' well‐being, although sometimes it does not.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research in the area of students' mental health demonstrates the positive relationship between academic grit and psychological well‐being (Jelińska & Paradowski, 2021 ; Lan & Moscardino, 2019 ; J. Li & Li, 2021 ) and the negative relationship between intolerance to uncertainty and psychological well‐being (Ulukan, 2021 ; Zhuo et al, 2021 ). Less is known about this relationship, mainly about the mediators, but these factors are important to understand why and how students' engagement improves students' well‐being, although sometimes it does not.…”
Section: Discussionmentioning
confidence: 99%
“…During the first wave of the pandemic, it was shown by comparing students from “health-related“ study programs to others that the former are less sensitive to changes in habits [ 4 ]. Furthermore, sport science students during the pandemic had a medium intolerance level of uncertainty, which also indicates that their behaviors and perceptions are moderate regarding the unknown factors about the future [ 23 ]. Moreover, they were physically active and maintained average scores in healthy lifestyle behaviors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the mental health concerns, the students had to face an unknown length of time of higher uncertainty and anxiety regarding their studies and career [ 20 , 21 , 22 ]. Although the pandemic led to uncertainty about the future, the sport science students’ intolerance level of uncertainty was moderate [ 23 ], which indicates that those types of students tend to have higher levels of adaptation. Moreover, sport science students compared to musicians tend to have more skills to face the challenges and obstacles that appear along their path [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Duman ( 2020 ), in a study, found that the fear and intolerance of uncertainty was at a moderate level among Turkish university students. Ulukan ( 2021 ) demonstrated that the level of intolerance of uncertainty among undergraduate sports students was average. Hussien et al ( 2020 ) indicated that undergraduate nursing students' intolerance of uncertainty levels was moderate during the pandemic.…”
Section: Discussionmentioning
confidence: 99%